Detailed guidance for issuing green bonds in developing countries
Provides guidance for bond issuers and their advisors on the process and key considerations for a successful green bond issuance. This publication covers all the steps required to follow best practices in labeling bonds as green. It includes examples, links to further details, and key resources for green bond issuers and their deal teams.